Functional Analysis of the Tomato Immune Receptor Ve1 through Domain Swaps with Its Non-Functional Homolog Ve2 - Fradin, Emilie F. (Public Library of Science, 2014)
Resistance in tomato against race 1 strains of the fungal vascular wilt pathogens Verticillium dahliae and V. albo-atrum is mediated by the Ve locus. This locus comprises two closely linked inversely oriented genes, Ve1 and Ve2, which encode cell surface receptors of the extracellular leucine-rich repeat receptor-like protein (eLRR-RLP) type. While Ve1 mediates Verticillium resistance through monitoring the presence of the recently identified V. dahliae Ave1 effector, no functionality for Ve2 has been demonstrated in tomato. Ve1 and Ve2 contain 37 eLRRs and share 84% amino acid identity, facilitating investigation of Ve protein functionality through domain swapping. In this study it is shown that Ve chimeras in which the first thirty eLRRs of Ve1 were replaced by those of Ve2 remain able to induce HR and activate Verticillium resistance, and that deletion of these thirty eLRRs from Ve1 resulted in loss of functionality. Also the region between eLRR30 and eLRR35 is required for Ve1-mediated resistance, and cannot be replaced by the region between eLRR30 and eLRR35 of Ve2. We furthermore show that the cytoplasmic tail of Ve1 is required for functionality, as truncation of this tail results in loss of functionality. Moreover, the C-terminus of Ve2 fails to activate immune signaling as chimeras containing the C-terminus of Ve2 do not provide Verticillium resistance. Furthermore, Ve1 was found to interact through its C-terminus with the eLRR-containing receptor-like kinase (eLRR-RLK) interactor SOBIR1 that was recently identified as an interactor of eLRR-RLP (immune) receptors. Intriguingly, also Ve2 was found to interact with SOBIR1.